Proses Interaksi Guru Dalam Membantu Siswa SMA Mengkonstruksi Pemahaman Konsep Peluang - Ratna Widyastuti; Abdur Rahman As’ari; Hery Susanto (Pascasarjana Universitas Negeri Malang (UM), 2015)
Abstract: The aim of the study is to describe teacher’s interaction in assisting students to construct their understanding of probability concept. This study employed descriptive research using a qualitative approach. The study was done by observing two times of probability lessons. The subjects were a teacher and 25 students. The data were collected using direct observation to see the teaching-learning process, and indirect observation using video, interview, and field note. The result of data analysis indicated that the availability of social and cognitive processes in the interaction. Based on verbal function, teacher’s interactions are having several functions, i.e: interrogative 54,26%, compositional 16,93%, informative 13,97%, reproductional 12,58%, expositional 12,24%, judgmental 9,91%, organizational 7,80%, and affective 6,99%. The interrogative and compositional functions are the most dominant interaction functions used by the teacher in assisting students’ understanding. Other interactions which assisting students’ understandings are informative, reproductional, expositional, judgmental, and affective. Key Words: interaction, types of interactions, constructing concept, probabilityAbstrak: Tujuan penelitian ini adalah mendeskripsikan interaksi guru dalam membantu siswa mengkonstruksi pemahaman konsep pada materi peluang. Jenis penelitian ini adalah penelitian deskriptif menggunakan pendekatan kualitatif. Penelitian dilakukan selama dua kali pembelajaran. Subjek adalah seorang guru dan siswa sebanyak 25 anak. Pengumpulan data dilakukan melalui observasi langsung dengan melihat pembelajaran dan observasi tidak langsung dengan melihat video melalui handy cam, wawancara, serta catatan lapangan. Berdasarkan hasil analisis disimpulkan bahwa terdapat proses sosial dan proses kognitif pada interaksi tersebut. Berdasarkan fungsi verbal menunjukkan bahwa percakapan guru memiliki fungsi sebagai berikut interrogative: 54,26 % , compositional: 16,93 % , informative: 13,97 %, reproductional: 12,58 % , expositional: 12,24 %, judgemental: 9,91 %, organisational: 7,8 %, affective: 6,99 %. Fungsi interrogatif dan compositional tampak mendominasi interaksi guru dalam membantu siswanya memahami konsep peluang. Interaksi lain yang juga mendukung pemahaman siswa adalah fungsi informative, reproductional, expositional, judgemental, dan affective. Kata kunci: interaksi, jenis interaksi, konstruksi konsep, peluang